Access to aidable residual hearing in adult candidates for cochlear implantation in the UK - Fielden, Claire A.; Hampton, Rosa; Smith, Sandra; Kitterick, Pádraig T. (Taylor & Francis, 2016)
Guidance from the National Institute for Health and Care Excellence (NICE) permits candidates to receive a cochlear implant provided they only hear sounds louder than 90 dB HL at 2 and 4 kHz. In some patients, their level of residual hearing may be sufficient to warrant the use of a hearing aid in their non-implanted ear. A survey of unilaterally-implanted adults indicated that those implanted since the publication of NICE guidance were almost seven times more likely to use a hearing aid than those implanted prior to this. If contralateral hearing aid use provides additional benefits over implant use alone, it may be appropriate to consider the capacity to use residual hearing following implantation when determining candidacy.